2021
DOI: 10.1007/s00406-021-01251-1
|View full text |Cite
|
Sign up to set email alerts
|

Online therapy: an added value for inpatient routine care? Perspectives from mental health care professionals

Abstract: Internet-delivered interventions can be effective in treating mental disorders. However, their rate of use in German psychiatric inpatient routine care is low. The current study aimed to investigate the attitude of mental health care professionals working in inpatient care regarding internet-delivered interventions, including presumed benefits, barriers and facilitators. In total, 176 health professionals from ten inpatient psychiatric hospitals throughout Germany were surveyed on site. The professionals’ atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Among European psychotherapists having mainly positive experiences with online consultations during the COVID-19 pandemic, De Witte et al ( 43 ) reported several barriers that might hinder implementation, such as data security issues or concerns about relational aspects, for instance impersonality and fostering a therapeutic alliance. In a study by Sander et al ( 86 ), German professionals reported having little experience or knowledge about internet-delivered interventions and the most frequently anticipated barriers were too severe symptoms of patients, the feared neglect of face-to-face contacts and insufficient technical equipment. The most frequently mentioned potential benefits were an optimized treatment structure and patient empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Among European psychotherapists having mainly positive experiences with online consultations during the COVID-19 pandemic, De Witte et al ( 43 ) reported several barriers that might hinder implementation, such as data security issues or concerns about relational aspects, for instance impersonality and fostering a therapeutic alliance. In a study by Sander et al ( 86 ), German professionals reported having little experience or knowledge about internet-delivered interventions and the most frequently anticipated barriers were too severe symptoms of patients, the feared neglect of face-to-face contacts and insufficient technical equipment. The most frequently mentioned potential benefits were an optimized treatment structure and patient empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature identifies several barriers to the implementation of e–mental health interventions in real-world settings [ 28 , 42 - 44 ], few reviews have focused on barriers to and facilitators of implementing eHealth interventions for informal caregivers [ 27 , 45 - 47 ]. To the best of our knowledge, no review has focused specifically on the implementation of e–mental health interventions for informal caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Main reasons for participating in the implementation study were a general interest in e-mental health and seeing it as a helpful add-on to regular treatment. This last reason was also seen by German professionals in inpatient care as an important benefit of e-mental health (24). Indeed, European organisations are aware of the potential benefits of e-mental health interventions but differ in terms of level of knowledge about these interventions and their feasibility within routine care.…”
Section: Discussionmentioning
confidence: 94%